Economic aspects of embedded SIM for the telecommunications consumer segment - Christian Wernick; Christin Isabel Gries (International Telecommunications Society (ITS), 2017)
After having been developed for Machine-to-Machine (M2M) communication, standardised embedded SIM (eSIM) solutions are about to be launched in the telecommunications consumer segment. At this early market stage, various details of eSIM implementation have not been fixed yet. Our paper aims to generate a well-founded understanding of characteristics and potential use cases and their likely impact on existing processes and market structures. Overall, eSIM seems unlikely to become a game changer in the mobile market in the short run. It offers, however, some potential to ease existing processes, improve customer satisfaction and generate new sources of revenues at different stages of the value chain.
Keywords: 330; Mobile; strategy; technological change